Investigasi keterampilan proses sains terintegrasi mahasiswa pendidikan fisika Universitas KH. A. Wahab Hasbullah - Sujarwanto, Eko; Putra, Ino Angga (Momentum: Physics Education Journal, 2018)
Abstract: Science arises and develops by including roles between theory and experiment. Physics, as part of science, is seen as a process, product, and attitude that is called the nature of science (Nature of Science / NOS). Learners obtain and construct science products in physics learning should pay attention to the NOS through Science Process Skills (SPS). This study aims to determine the level of students' understanding of integrated SPS, namely identifying and controlling variables, hypothesizing, operationally defining, graphing and interpreting data, and designing experiments. The research conducted was descriptive quantitative research with survey methods. The research subjects were students of physics teacher candidates at the University of KH. A. Wahab Hasbullah. The results showed that the integrated SPS student physics teacher candidates were still low with an average of 60.20. This shows that students have not yet reached the level of formal operational cognitive development and have not been strong in basic SPS. Students have the highest ability in the aspect of formulating hypotheses while the lowest aspects are operationally defined. An integrated effort needs to be made to increase SPS for students. Abstrak: Sains muncul dan berkembang dengan menyertakan peran antara teori dan eksperimen. Fisika, sebagai bagian dari sains, dipandang sebagai proses, produk, dan sikap yang disebut sebagai hakikat sains (Nature of Science/NOS). Peserta didik memperoleh dan mengkonstruk produk sains di pembelajaran fisika seharusnya memperhatikan NOS melalui Keterampilan Proses Sains (KPS). Penelitian ini bertujuan mengetahui tingkat pemahaman mahasiswa terhadap KPS terintegrasi yaitu mengidentifikasi dan mengontrol variabel, berhipotesis, mendefinisikan secara operasional, membuat grafik dan menginterpretasikan data, serta mendesain eksperimen. Penelitian yang dilakukan adalah penelitian kuantitatif deskriptif dengan metode survei. Subjek penelitian adalah mahasiswa calon guru fisika di Universitas KH. A. Wahab Hasbullah. Hasil penelitian menunjukkan KPS terintegrasi mahasiswa calon guru fisika masih rendah dengan rata-rata 60,20. Hal ini menunjukkan bahwa mahasiswa belum sampai pada tingkat perkembangan kognitif operasional formal dan belum kuat pada KPS dasar. Mahasiswa memiliki kemampuan paling tinggi pada aspek merumuskan hipotesis sedangkan paling rendah aspek mendefinisikan secara operasional. Usaha terpadu perlu dilakukan untuk meningkatkan KPS pada mahasiswa.